Kandungan logam berat dalam sedimen di Perairan Teluk Wawobatu, Kendari, Sulawesi Tenggara - Edward . (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2014)
Abstract. Examination of heavy metals content in sediment ofWawobatu Bay Waters, Kendari wasconducted in June2011. Sediment sampleswere collectedusing gravitycoreat 5research stations. Heavymetals content weremeasuredusingAtomic Absorption Spectrophotometer (AAS). The purpose of this research wasto examine the heavy metals content in sediment and to predict the quality of sediment based on index analysis approach (geoaccumulation index and pollution load index). The results showed that Pb was rangedfrom 3.704 pp to 21.892 ppm, Cd was 0.784-1,385 ppm, Cu was 3,451-12,193 ppm, and 24.838 ppm, to 69.973 ppm and 37.289 ppm to 72.329 ppm for Zn and Ni, respectively. It is concluded that the content of the theseheavy metals were lower compared to threshold value stated by The Stated Ministry Office for Life Environment 2004 and Ontario sediment Guideline 2008. In general the heavy metals content in Station 4 was higherthanthe other stations. This iscaused by the differences insediment texture in each station, whilestation 4 is situated in estuary and it has a black clayssediment texture. In addition, the content of Ni washigher than the others examined heavy metals.Based on I-geo values that thesediment in this waters is categorized asunpolluted by Pb, Cu, Zn, and Ni (I-geo0), and moderate polluted category by Cd (1I-geo2). In addition,based on PLI values, sediments of Wawobatu bay was unpolluted by Pb, Cu, Zn, Ni and Cd.Keywords: Heavy metals; sediments; Wawobatu Bay; KendariAbstrak. Pengamatan kandungan logam berat dalam sedimen diPerairanTeluk Wawobatu, Kendari telah dilakukan pada bulan Juni 2011. Contoh sedimen diambil dengan menggunakan gravity core pada 5 stasiun penelitian. Kandungan logam berat diukur dengan menggunakan Spektrofotometer Serapan Atom (SSA). Tujuan penelitian ini adalah untuk mengetahui kandungan logam berat dalam sedimen serta memprediksi kualitas sedimen berdasarkan pendekatan analisis indeks (Indeks geoakumulasi dan Indeks Beban Pencemaran).Hasilnya menunjukkan, kandungan Pb berkisar 3,704-21,892 ppm, Cd 0,784-1,385 ppm, Cu 3,451-12,193 ppm, Zn 24,838-69,973 ppm, dan Ni 37,289-72,329 ppm. Kandungan ke lima logam tersebut masih lebih rendah dari nilai ambang batas yang ditetapkan oleh Kantor Menteri Negara Lingkungan Hidup 2010 dan baku mutu sedimen Ontario (Ontario Sediment Guideline) 2008. Kandungan logam berat dalam sedimen di Stasiun 4 lebih tinggi dibandingkan dengan Stasiun lainnya. Hal ini disebabkan oleh perbedaan tekstur sedimen di masing-masing stasiun. Stasiun 4 berada di muara sungai dan mempunyai sedimen dengan tekstur berupa lumpur berwarna hitam.Kandungan logam Ni lebih tinggi dibandingkan dengan yang lain, hal ini menunjukkan adanya masukan sedimen dari Teluk Kendari dan Teluk Lasolo yang terbawa oleh arus, disamping yang berasal dari darat yang masuk melalui aliran sungai. Berdasarkan nilai indeks geoakumulasi (I-geo)sedimen di perairan ini termasuk kategori tidak tercemar oleh Pb, Cu, Zn, dan Ni (I_geo0), dan tercemar sedang oleh Cd (1I_geo2).Namun berdasarkan nilai indeks beban pencemaran (PLI), sedimen di perairan ini belum tercemar oleh logam berat Pb, Cd, Cu, Zn, dan Ni.